1982
DOI: 10.1017/s0043174500040832
|View full text |Cite
|
Sign up to set email alerts
|

Metolachlor and Alachlor Effects on Membrane Permeability and Lipid Synthesis

Abstract: Metolachlor [2-chloro-N-(2-ethyl-6-methylphenyl)-N-(2-methoxy-1-methylethyl)acetamide] at 1 × 10−5and 1 × 10−4M increased the leakage of previously absorbed,32P-labeled orthophosphate from the roots of onion (Allium cepaL.), a susceptible species, by 14 and 41 times the control values, respectively. A significant amount of32P leaked from the roots of the moderately susceptible species, cotton (Gossypium hirsutumL. ‘DPL 61′) and cucumber (Cucumis sativusL. ‘Ashley′), whereas no significant loss of32P occurred f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Since dioxane/HCl was originally used to isolate cell wall constituents (Langebartels and Harms, 1985) and to solubilize sporopollenin (Couderchet et al, 1996), we assume the VLCFAs hydrolysed by this method originate from the plasma mem brane and the cell wall. Accordingly, metolachlor increased the membrane permeability of cucumber roots as reported by Mellis et al (1982). This may be re lated to the synthesis of VLCFAs assumed to be crucial structure param eters for the stability of membranes (Cook, 1996;Ho et al, 1995).…”
Section: Discussionsupporting
confidence: 60%
“…Since dioxane/HCl was originally used to isolate cell wall constituents (Langebartels and Harms, 1985) and to solubilize sporopollenin (Couderchet et al, 1996), we assume the VLCFAs hydrolysed by this method originate from the plasma mem brane and the cell wall. Accordingly, metolachlor increased the membrane permeability of cucumber roots as reported by Mellis et al (1982). This may be re lated to the synthesis of VLCFAs assumed to be crucial structure param eters for the stability of membranes (Cook, 1996;Ho et al, 1995).…”
Section: Discussionsupporting
confidence: 60%
“…At the biochemical level, lipid synthesis appears to be the most sensitive biosynthetic pathway for this group (Chang, Ashton & Bayer, 1985;Mellis et al, 1982). An increased membrane permeability observed by Mellis et al (1982) and by Sloan (1985) might be a consequence of effects on lipid biosynthesis.…”
Section: Chloroacetamidesmentioning
confidence: 99%
“…At the biochemical level, lipid synthesis appears to be the most sensitive biosynthetic pathway for this group (Chang, Ashton & Bayer, 1985;Mellis et al, 1982). An increased membrane permeability observed by Mellis et al (1982) and by Sloan (1985) might be a consequence of effects on lipid biosynthesis. Wilkinson (1982Wilkinson ( , 1985 observed an inhibition of gibberellin biosynthesis and suggested that the a-chloroacetamides inhibit mono-oxygenases.…”
Section: Chloroacetamidesmentioning
confidence: 99%
“…Reinhardt (1) membranes, double membranes of chloroplasts and membranes of nuclei in sorghum. Similarly, Mellis et al (1982) reported that metolachlor and alachlor affected the membrane permeability. Malan et al (1985) reported that atrazine affected ultrastructure of maize leaves.…”
Section: Control Treatedmentioning
confidence: 89%
“…Reinhardt & Nel (1986) reported that alach10r-treated sorghum (Sorghum bicolor L.) plants showed disintegration of cell vacuole membranes, double membranes of chloroplasts and membranes of nuclei. Mellis et al (1982) found no evidence that the loss of cotton (Gossypium hirsutum L.) and maize root cell membrane integrity is due to the inhibition of total lipid, phospholipid or phosphatidylcholine (PC) synthesis by either alachlor or metolachlor. Similar work has been done on other plant species and herbicides to describe the effects of herbicides on the ultrastructure of root and shoot cells.…”
Section: Introductionmentioning
confidence: 99%